2013
DOI: 10.1007/s11096-013-9822-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L’Aquila earthquake on the prescribing pattern of antidepressant and antipsychotic drugs

Abstract: The earthquake determined a short-term increase in the use of antipsychotics (mostly haloperidol and promazine) and, to lesser extent, of antidepressants (i.e. tryciclics), especially in older women of L'Aquila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 25 publications
5
19
1
5
Order By: Relevance
“…In the present study, we observed that the population of Ansan Danwon showed significantly greater increases in the prescription rate of antidepressants compared that in a control community after the Sewol Ferry disaster. Our study result is consistent with previous pharmaco-epidemiological studies reporting increased prescription rates of antidepressants after disasters including a cyclone, earthquake, and terrorist attack (DiMaggio et al, 2007;Rossi et al, 2011;Trifiro et al, 2013;Usher et al, 2012). DiMaggio et al investigated the prescription rate of SSRIs among New York State Medicaid enrollees living within 3 miles of the World Trade Center before and after the terrorist attacks of September 11, 2001 and found that prescription rate of SSRIs during 3 months after the disaster was increased compared to that during the previous 8-month period (DiMaggio et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we observed that the population of Ansan Danwon showed significantly greater increases in the prescription rate of antidepressants compared that in a control community after the Sewol Ferry disaster. Our study result is consistent with previous pharmaco-epidemiological studies reporting increased prescription rates of antidepressants after disasters including a cyclone, earthquake, and terrorist attack (DiMaggio et al, 2007;Rossi et al, 2011;Trifiro et al, 2013;Usher et al, 2012). DiMaggio et al investigated the prescription rate of SSRIs among New York State Medicaid enrollees living within 3 miles of the World Trade Center before and after the terrorist attacks of September 11, 2001 and found that prescription rate of SSRIs during 3 months after the disaster was increased compared to that during the previous 8-month period (DiMaggio et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Low-dose antipsychotics are commonly prescribed for the treatment of anxiety, agitation, depression, or insomnia (Rossi et al, 2011). Consistent our results, several pharmaco-epidemiological studies have reported significant increases in the prescription rates of antipsychotics after a disaster (Rossi et al, 2011;Trifiro et al, 2013). With regard to the short-term effects of the disaster, we similarly did not identify any significant differences in psychotropic medication prescription rates between Ansan Danwon and Cheonan city after the disaster.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…11 Monitoring prescription drug changes can provide an indirect measure of psychological distress in the population. [14][15][16] Psychological stress has been associated with externalized behaviour such as substance abuse and violence. 17 An increase in violence following a disaster has been observed in some studies.…”
mentioning
confidence: 99%